Residual stress measurement in PVD optical coatings by microtopography - Costa, Manuel F. M. (2011)
Residual stress in optical plasma vapor deposited coatings must be carefully measured. The topographic inspection of the coatings’ surface at microlevel allows the assessment of its residual stress. In the present work we will report on the optical non-destructive and non-invasive microtopographic inspection of WO3 PVD thin films for residual stress evaluation. The MICROTOP.06.MFC system, an active optical triangulation sensor developed at the Universidade do Minho, was employed. It allows depth resolutions down to 2 nm and lateral resolutions down to 1 μm. The three dimensional coordinate set obtained on the inspection allow the calculation of the stress distribution over the film.